Pengaruh Pengembangan Wisata Dan Promosi Terhadap Tingkat Kunjungan Wisatawan Pada Obyek Wisata Air Panas Cipari Kabupaten Cilacap - Agus Riyadi; Ferey Herman (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This research is motivated by the not yet optimal development of the Cipari Hot Spring area destination in Cilacap Regency, this can be seen from the lack of facilities and infrastructure that can support tourism development, such as lodging places for tourists, information facilities and banking. The trend of visitor visits to Cipari Hot Springs has decreased significantly, namely 64% in 2020. This study aims to determine 1) the effect of Tourism Development on Tourist Visit Rates, 2) the effect of Promotion on Tourist Visit Rates, and 3) the influence of Tourism Development and Promotion jointly on the Level of Tourist Visits at the Cipari Hot Spring Tourism Object, Cilacap Regency. This research uses quantitative research methods. The results of the study show that there is an influence of Tourism Development on the Level of Tourist Visits, there is an influence of Promotion on the Level of Tourist Visits, and there is an effect of Tourism Development and Promotion together on the Level of Tourist Visits at the Cipari Hot Spring Tourism Object, Cilacap Regency. This means that the better the Tourism Development and Promotion, the more tourist visits will increase, and vice versa.